Synthesis and Characterization of the Ligand Based on Benzimidazole and Its Copper Complex: DNA Binding and Antioxidant Activity - Huilu Wu; Fan Kou; Fei Jia; Bin Liu; Jingkun Yuan; Ying Bai (Bioinorganic Chemistry and Applications)
A new copper(II) complex with formulae of [Cu(buobb)2](pic)2, where buobb stands for the ligand of 1,3-bis(1- butylbenzimidazol-2-yl)-2-oxopropane and pic represents 2,4,6-trinitrophenol, has been synthesized and characterized by elemental analyses, molar conductivity, IR, UV-Vis spectra measurements, and cyclic voltammetry. The crystal structure of the copper(II) complex has been determined by X-ray single-crystal diffraction. The coordination environment around each copper(II) atom can be described as a distorted octahedral geometry. The π-π stacking interactions link the copper(II) complex into a 1D infinite network. The interactions of the ligand and the copper(II) complex with calf thymus DNA (CT-DNA) are investigated by using electronic absorption titration, ethidium bromide-DNA displacement experiments, and viscosity measurements. Additionally, the copper(II) complex’s antioxidant properties have been investigated in vitro.